Short Communication: Screening the potency of Zingiberaceae leaves as antioxidant and antiaging agent - UMMI ZAHRA; YUNI KARTIKA; IRMANIDA BATUBARA; LATIFAH K DARUSMAN; AKHIRUDDIN MADDU (Smujo International, 2016)
Abstract. Zahra U, Kartika Y, Batubara I, Darusman LK, Maddu A. 2016. Short Communication: Screening the potency of Zingiberaceae leaves as antioxidant and antiaging agent. Nusantara Bioscience 8: 221-225. Zingiberaceae is a family of plant with antioxidant, anticancer, and antiaging activities. The use of the leaves part of this family has never been explored. Therefore, the aim of this research is to evaluate the antioxidant and antiaging activities of some Zingiberaceae’s leaves. The species of Zingiberaceae used in this study are Alpinia galanga (L), Curcuma aeruginosa Roxb, Curcuma longa L, Curcuma zedoaria, Curcuma xanthorrhiza Roxb, Boesenbergia rotunda (L.), Elettaria cardamomum, Zingiber zerumbet, Zingiber officinale Roscoe, and Zingiber purpureum Roscoe. Leaves were extracted with 2 different solvents sequentially: ethyl acetate and methanol. Total phenolic and flavonoid contents of the extracts were determined spectrophotometrically. Antioxidant activities were tested by using DPPH (2,2-diphenyl-1-picrylhydrazyl ) and ABTS (2,2'-azino-bis-3-ethyl benzothiazoline-6-sulfonic acid), whilst antiaging activity was tested by using antiglycation method. The results showed that the flavonoid content of the extracts was in the range of 0.83-25.17 g QE/100 g extract with total phenolic content ranging from 9.80-91.71 GAE mg/100 mg extract. The methanol extract of Curcuma xanthorrhiza displayed the highest antioxidant capacity in the DDPH (IC50 282.35 mg/mL) and TEAC (10.08%) assays, followed by the ethyl acetate extract of C. longa, ethyl acetic extract of C. xanthorrhiza and methanol extract of Z. officinale, while the most active antiglycation is the methanol extract of Z. officinale (IC50 203.85 mg/L).